Genetic Variation for Nitrogen Use Efficiency Traits in Global Diversity Panel and Parents of Mapping Populations in Pearl Millet - Pujarula, Vijayalakshmi; Pusuluri, Madhu; Bollam, Srikanth; Das, Roma Rani; Ratnala, Rambabu; Adapala, Gopikrishna; Thuraga, Vishnukiran; Rathore, Abhishek; Srivastava, Rakesh K.; Gupta, Rajeev (Frontiers in Plant Science, 2021)
Nitrogen (N) is one of the primary macronutrients required for crop growth and productivity. This nutrient is especially limiting in the dry and infertile soils where pearl millet [Pennisetum glaucum (L.) R. Br] is typically grown. Globally, pearl millet is the sixth most important cereal crop which is grown by subsistence farmers in the arid and semi-arid regions of sub-Saharan Africa and the Indian subcontinent. Most of the agro-ecologies have low N in the root zone soil strata in these regions. Therefore, there is an immense need to identify lines that use nitrogen efficiently. A set of 380 diverse pearl millet lines consisting of a world diversity panel (345), mapping population parents (20), and checks (15) were evaluated in an alpha-lattice design with two replication, 25 blocks, three-row plot for 11 nitrogen use efficiency (NUE) related traits across three growing seasons under different N regimes (N0, N50, N100). Analysis of variance revealed significant genetic variation for NUE across treatments and years. Nitrogen in limited condition (N0) resulted in 27.6% and 17.6% reduction in grain yield (GY) and dry stover yield (DSY) as compared to N50. More reduction of GY and DSY traits by 24.6% and 23.6% were observed under N0 as compared to N100. Among the assessed traits, GY exhibited significant positive correlations with nitrogen utilization efficiency (NUtE) and nitrogen harvest index (NHI), indicates the pivotal role of N remobilization to the grain in enhancing yield rates. Top 25 N-insensitive (NIS) & least (N-sensitive (NS) genotypes were identified under low N conditions. Out of 25 NIS lines, nine genotypes (IP 10820, IP 17720, ICMB 01222-P1, IP 10379, ICMB 89111-P2, IP 8069, ICMB 90111-P2, ICMV IS89305 and ICMV 221) were common with the top 25 lines at N100 level showing the genotype plasticity under N0 & N100 conditions. Results from the current investigation will help in deploying the identified low N tolerant genotypes as a source of donor material in breeding programs. Further, the obtained results may help in the identification of genomic regions responsible for NUE and its deployment in breeding programs through marker-assisted selection (MAS).